Spectrum of ocular manifestations in cobalamin C and cobalamin A types of methylmalonic acidemia. (1st October 2016) - Ku, Cristy A.; Ng, Jacqueline K.; Karr, Daniel J.; Reznick, Leah; Harding, Cary O.; Weleber, Richard G.; Pennesi, Mark E.
ABSTRACT: Background : Cobalamin C disease (cblC), which leads to methylmalonic acidemia with homocystinuria, is the most common inherited disorder of vitamin B12 metabolism. Reported ocular findings associated with cblC have been maculopathy, pigmentary retinopathy, and optic nerve atrophy. Cobalamin A disease (cblA) which causes an isolated methylmalonic acidemia without homocystinuria is rarer than cblC. This is the first detailed report of the ocular findings associated with cblA. We also describe the spectrum of ocular findings in our cblC patients. Materials and methods : A case series describing the ophthalmologic clinical course of six patients with a diagnosis of cobalamin C type and one patient with cobalamin A type of methylmalonic acidemia. Patients were diagnosed through biochemical laboratory testing and genetic analysis was conducted on most patients. Longitudinal fundus findings, optical coherence tomography (OCT), autofluorescence, and electrophysiology were followed in the patients. Results : The cblA patient demonstrated a relatively mild ocular phenotype with late-onset and slowly progressing temporal disc pallor and peripapillary atrophy in the second decade of life. The patient maintained good visual acuity and central vision, without evidence of maculopathy. The six cblC patients demonstrated a range of ocular findings from unremarkable and mild phenotypes to significant retinopathy, including bull's eye maculopathy, severe maculopathy with punched out chorioretinal atrophy, peripheral bone spicules, and optic nerve atrophy. Conclusions : The spectrum of ocular manifestations seen with inherited disorders of cobalamin metabolism is wide, ranging from mild optic nerve atrophy to severe macular or retinal degeneration. This heterogeneity may in part reflect the associated biochemical phenotype, such as that observed between our cblA and cblC patients. We also observed heterogeneity within the cblC type in agreement with previous reports.